STRUGGLE FOR A BETTER LIFE IN LOUISA MAY ALCOTT'S LITTLE WOMEN - Gabriela Nadya Rompis; Ignatius J C Tuerah; Merlin M Maukar (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study is to reveal struggle in Little Women by Louisa May Alcott. In conducting this study, the writers delimit only in revealing Josephine’s struggle for a better life. This research is qualitative research. The data are collected in form of words or picture rather than numbers. The data are taken only from the work itself and to see the interrelationship between the elements of the novel. The result of this study is to show the struggle of Jo for a better life. The first struggle is about Jo’s family, the second is struggle for Jo’s goals, and the last one is struggle in her love. Jo was motivated from the condition around her, so she wants to earn money to help her family financial, and make herself achieve the dream. Based on the result of this study, it can be concluded that the novel Little Women by Louisa May Alcott teaches that struggle is a part of human life, so do not give up to achieve any good things all human beings heart's desire.